Scenario-guided policy development in Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Ugandan policy makers came together from 20 to 21 February in Jinja, Uganda for a workshop that focused on scenario-guided policy development in the context of climate change to work on an implementation plan for Uganda’s National Agricultural Policy and revision of the Mechanization Framework. This workshop is part of CCAFS’ PACCA project (Policy Action for Climate Change Adaptation) and was organised in collaboration with the University of Oxford. Photos: E. van de Grift.